Does coping mediate the relationship between competitive anxiety and eating disorders in athletes? - Fortes, L. de S.; do Nascimento Junior, J. R.; Freire, G. L. M.; Ferreira, M. E. C. (Psicologia: teoria e prática, 2020)
The competitive anxiety shows positive and linear relationship with risk behaviors for eating disorders (RBED). The competitive anxiety shows negative and linear relationship with coping strategies. Perhaps the coping strategies can mediate the relationship between competitive anxiety and RBED in athletes. The aim of this study was to analyze the coping mediation between competitive anxiety and RBED in Brazilian male athletes. 739 athletes from various sports participated. To assess the RBED frequency, the Disordered Eating in Sports Scale was adopted. The Brazilian version of the Competitive State Anxiety Inventory was used to evaluate competitive anxiety. Athletic Coping Strategies Inventory was used to evaluate coping strategies. The findings revealed a direct relationship between competitive anxiety and RBED (p = .01). The results indicated that coping strategies potentiated the relationship between competitive anxiety and RBED (p = .01). It was concluded that coping can be considered a psychological determinant in the relationship between competitive anxiety and RBED.